Fostering EFL/ESL Students’ Language Achievement: The Role of Teachers’ Enthusiasm and Classroom Enjoyment - Liu, Yang; Zhang, Mingjie; Zhao, Xuetao; Jia, Fang (Frontiers in Psychology, 2021)
Thanks to the inflow of positive psychology (PP) in language education in general and language learning in particular, extensive consideration has been drawn to the role of emotion in second language acquisition (SLA). Enjoyment as a mutual constructive sensation experienced by students has engrossed academic attention. Likewise, teachers are redirected as the most remarkable figure of any educational association, and their enthusiasm is substantial for students in the classroom. In line with the inquiries of teacher enthusiasm, principles of PP, and classroom enjoyment, the current review strives for this form of connection and its impacts on learners’ achievement. Subsequently, the suggestions of this review for teachers, learners, and educator trainers are deliberated.